2011
DOI: 10.1590/s1517-83822011000100030
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of enterotoxigenic E. coli isolated from the stools of children aged 0-10 years with diarrhea in mid-anatolia region, Turkey

Abstract: The stool samples from 245 patients with diarrhea were tested for heat labile toxin (LT) and heat stable toxins (ST) by passive latex agglutination and enzyme immunoassay methods respectively. Twelve (4.9%) enterotoxigenic E. Coli ETEC strains were isolated. Five strains (2%) expressed ST, and 7 (2.8%) expressed LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
3
2
0
1
Order By: Relevance
“…The overall prevalence of ETEC under 5 years old, in this study was ~19%. The isolation rates of ETEC in our study is similar to previous studies that have reported the prevalence of ETEC in developing countries from Bangladesh, Turkey, Peru, Mexico, Egypt, Argentina, India, Nicaragua, and Tunisia which indicated a rate of 18-38% in children [20][21][22][23][24]. However, the ETEC prevalence in our study was lower than what was reported in a previous study (40.7%) conducted in Zambia [18] using Luminex Magpix GPP panel which uses x-TAG technology.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 90%
“…The overall prevalence of ETEC under 5 years old, in this study was ~19%. The isolation rates of ETEC in our study is similar to previous studies that have reported the prevalence of ETEC in developing countries from Bangladesh, Turkey, Peru, Mexico, Egypt, Argentina, India, Nicaragua, and Tunisia which indicated a rate of 18-38% in children [20][21][22][23][24]. However, the ETEC prevalence in our study was lower than what was reported in a previous study (40.7%) conducted in Zambia [18] using Luminex Magpix GPP panel which uses x-TAG technology.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 90%
“…The overall prevalence of ETEC under 5 years old, in this study was ~19%. The isolation rates of ETEC in our study is similar to previous studies that have reported the prevalence of ETEC in developing countries from Bangladesh, Turkey, Peru, Mexico, Egypt, Argentina, India, Nicaragua, and Tunisia which indicated a rate of 18-38% in children [22][23][24][25][26]. However, the ETEC prevalence in our study was lower than what was reported in a previous study (40.7%) conducted in Zambia [18] using Luminex Magpix GPP panel which uses x-TAG technology.…”
Section: Discussionsupporting
confidence: 90%
“…Heat-stable and heat-labile enterotoxins encoded by heat-stable enterotoxin (estA) and heat-labile enterotoxin (eltA) genes, respectively, are responsible. These genes can be easily detected by serological assays [39] and multiplex DEC PCR.…”
Section: Common E Coli Pathotypesmentioning
confidence: 99%